FORMULA SEHAT TINGGI PROTEIN (NDPCAL 7), FE DAN BETAKAROTEN DARI PANGAN LOKAL DALAM UPAYA PEMENUHAN FE DAN VITAMIN A PADA ANAK MALNUTRISI SEKOLAH DASAR DI KECAMATAN MAPANGET KOTA MANADO - Jufri Sineke; Olga Lieke Paruntu; Jeineke Ratuele (Jurnal GIZIDO, 2016)
Malnutrition is a condition in which the body experiences an interruption in the use ofnutrients for growth, development and activity. Malnutrition can be caused by a lack offood intake or disrupted absorption, digestion and utilization of nutrients in the body. Thegeneral objective of this study is a healthy high-protein formula socialize, Fe and betacarotene in order to fulfill the needs of Fe and Vitamin A primary school children. Thistype of research is quasy pre and post test experiment one group design. This studydescribes the differences in body weight, nutritional status, intake of energy, protein,vitamin A and Fe in primary school students before and after the intervention. Theexperiment was conducted in the District Mapanget Manado City in May s / d November2015. The sample was determined based on the formula Estimating the differencebetween two population proportion of 81 samples. Data include sample characteristics,anthropometric and nutrient intake. Processing and analysis of univariate data todetermine the distribution and characteristics of the sample. Bivariate analysis using adifferent test to determine differences in body weight, nutritional status, intake of energy,protein, vitamins and Fe before and after the intervention. Interpretation of the datapresented in tables, charts and discussion.The results showed no significant difference between the weight before and after theintervention, where there is a weight gain of 0.40 kg, there is a very significant differencebetween energy intake before and after the intervention, where an increase in the intakeof 230.55 Calories, there are differences significant between protein intake before andafter the intervention, where an increase in protein intake of 9.96 g, there is a verysignificant difference between the intake of vitamin A before and after the intervention,where an increase in vitamin A intake amounted to 202.95 RE, there are very significantdifferences between the intake of Fe before and after the intervention, where an increasein the intake of Fe at 1:02 mg, and there are significant differences between the IMT / Ubefore and after the intervention, with an increase in BMI / U at 0.320.